The Raven King - Stiefvater, Maggie, 1981- (2016)
Not believing in true love, Blue never thought the warning that she will cause her true love's death would be a problem, but as her life is entangled in the world of the Raven Boys, she's not so sure anymore
9-12
Keywords: Clairvoyance -- Juvenile fiction; Magic -- Juvenile fiction; Dreams -- Juvenile fiction; Romance fiction; Fantasy; Fantasy